#### Answer

$-4dg-12d+2g$

#### Work Step by Step

To simplify, expand the terms:
$(2-d)g-3d(4+g)=2g-dg-12d-3dg=-4dg-12d+2g$.

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

$-4dg-12d+2g$

To simplify, expand the terms:
$(2-d)g-3d(4+g)=2g-dg-12d-3dg=-4dg-12d+2g$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.